Adopting Animal Identification Systems and Services in Kansas Auction Markets: Costs, Opportunities, and Recommendations - Bolte, Kati; Dhuyvetter, Kevin C.; Schroeder, Ted C.; Rickard, Bryan (Kansas State University. Agricultural Experiment Station and Cooperative Extension Service, 2010)
There is growing interest in adopting electronic animal identification services at livestock markets. The National Animal Identification System (NAIS) has provided broad recognition of the need for, and supplied momentum for development of, premises registration and associated animal identification systems. Furthermore, specialized marketing programs that target beef products to particular customer markets, especially export trade, are increasingly requiring individual animal identification. Livestock markets are a major center for cattle trade as 80 percent of feeder cattle sales occur through local auction markets or video auctions. For disease tracing and control reasons, animal identification systems become especially important at the time cattle are marketed. When an animal leaves its farm or ranch of origin is when recording individual animal identification and movement information begins. Thus, it is likely that livestock auctions will be a primary industry segment where animal identification and movement information is electronically recorded. Because of the high percentage of cattle marketed through livestock markets, electronic individual animal identification scanning may be an important addition at auction facilities.
Keywords: Radio frequency identification; RFID; Electronic animal identification; National Animal Identification System; NAIS; Animal tracing; Livestock markets; Logistics; Costs